1993
DOI: 10.1123/ijsn.3.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Loss in Sweat of Athletes Exercising in Hot and Neutral Temperatures

Abstract: (Zn) loss from sweat of 9 male and 9 female athletes exercising under (35OC, HE) and neutral (25OC, NE) conditions was examined. Subjects ed at 3% V0,max on a cycle ergometer for 1 hr during each trial.e sweat samples were analyzed for Zn by atomic absorption spectroThere was a significant interaction of time, gender, and temperaole-body sweat rates (WBSR). WBSR for males were higher trials and at each time. WBSR from the second half of exercise re higher than those from the first half for both sexes and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
5
18
1
1
Order By: Relevance
“…Therefore, there were no significant differences in the loss of any of the examined trace elements between summer and winter. These results agreed with the results of Tipton et al (19) and Mary & Haymes (20) in which there were no differences in the loss of Zn and Fe by sweating during exercise at the same load between neutral (25°C) and hot environments (35°C).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, there were no significant differences in the loss of any of the examined trace elements between summer and winter. These results agreed with the results of Tipton et al (19) and Mary & Haymes (20) in which there were no differences in the loss of Zn and Fe by sweating during exercise at the same load between neutral (25°C) and hot environments (35°C).…”
Section: Discussionsupporting
confidence: 83%
“…Tipton et al (19) reported that there was no significant differences in the loss of Zn due to exercise between 25°C and at 35°C, because the concentration of Zn in the sweat at the exercise of 70-75% VO 2 max for one hour was lower at 35°C than at 25°C, but the amount of sweat was about two times larger at 35°C than at 25°C. Mary & Haymes (20) also reported no difference in the loss of Fe by sweating during exercise between 25°C at 35°C, because the concentration of Fe in the sweat while exercising at 50% VO 2 max for one hour was lower at 35°C than at 25°C but the quantity of sweat was larger at 35°C than at 25°C.…”
Section: Discussionmentioning
confidence: 99%
“…24 It was noted that moderate exercise increased zinc loss with perspiration in athletes, but the amount of loss may be more in males, relative to females. 25 This situation may be associated with urinary zinc loss resulting from skeletal muscle protein breakdown observed in athletes who train regularly. Cordova and Alvarez 26 reported that muscle zinc concentration declined as a consequence of a low plasma concentration in athletes.…”
Section: Resultsmentioning
confidence: 99%
“…An estimate of 0.5 mg/day for men was obtained from studies of whole body surface zinc losses in men (Jacob et al, 1981;Milne et al, 1983;Johnson et al, 1993). The estimate of 0.3 mg/day for women was calculated by multiplying the value for men by the female to male ratio of sweat zinc losses observed in studies of whole body sweat zinc losses and whole body sweat rates in men and women (Cohn and Emmett, 1978;Avellini et al, 1980;Frye and Kamon, 1983;Tipton et al, 1993;DeRuisseau et al, 2002;Hazelhurst and Claassen, 2006). These studies reported female to male ratios for sweat zinc loss rates between 0.5 and 0.7, while sweat zinc concentrations were similar.…”
Section: Estimation Of Endogenous Zinc Lossesmentioning
confidence: 99%